2017
DOI: 10.1177/0146167217705120
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Influences Between Loneliness and Self-Centeredness: A Cross-Lagged Panel Analysis in a Population-Based Sample of African American, Hispanic, and Caucasian Adults

Abstract: Loneliness has been posited to increase the motivation to repair or replace deficient social relationships and, seemingly paradoxically, to increase the implicit motivation for self-preservation. In the current research, we report a cross-lagged panel analysis of 10 waves of longitudinal data ( N = 229) on loneliness and self-centeredness (as gauged by Feeney and Collins's measure of chronic self-focus) in a representative sample of middle-aged and older adults. As predicted by the proposition that loneliness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 40 publications
3
67
1
Order By: Relevance
“…Of further interest is the relationship between awe and prosocial behaviour demonstrated in previous research [14,43] showing that vast (nature) interactions can reduce self-centredness and instead make people feel more connected to others. In line with this notion, a longitudinal study revealed a relationship between self-centredness and loneliness [1]. These combined findings underscore the importance of stimulating awe and related feelings of connectedness with others and the world at large amongst people struggling with loneliness and social isolation.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Of further interest is the relationship between awe and prosocial behaviour demonstrated in previous research [14,43] showing that vast (nature) interactions can reduce self-centredness and instead make people feel more connected to others. In line with this notion, a longitudinal study revealed a relationship between self-centredness and loneliness [1]. These combined findings underscore the importance of stimulating awe and related feelings of connectedness with others and the world at large amongst people struggling with loneliness and social isolation.…”
Section: Discussionsupporting
confidence: 53%
“…Loneliness, both amongst young people and older adults, is increasingly recognized as a serious public health concern [1]. Apart from its negative effect on mood and (mental) wellbeing, loneliness can have serious effects on physical health, including greater risk of cardiovascular disease [2] and accelerated physiological decline [3].…”
Section: Introductionmentioning
confidence: 99%
“…Feeling socially isolated or lonely is dangerous and threatening because of the lack of protection and assistance of others. This experience promotes an emphasis on short‐term self‐preservation, which includes increased hypervigilance for social threats and increased self‐focus or self‐centeredness, that is, a heightened concern for one's own interests . This concern may lead lonely people to avoid others to protect themselves from further rejection, as well as feel less desire to affiliate, which causes them to miss out on opportunities for reconnection and rewarding social interactions .…”
Section: Emergence and Maintenance Of Lonelinessmentioning
confidence: 99%
“…Loneliness, defined as a discrepancy between one’s desired and achieved levels of social connectedness [ 1 ], has been found to impact behavioral processes related to attention, executive function, and social cognition (for review, see [ 2 ]). Recently, it has been hypothesized that loneliness may also influence preferences for interpersonal distance, that is, the preferred space between people in proximal space [ 3 , 4 ]. Interpersonal distance corresponds to "an area with an invisible boundary surrounding a person's body, into which intruders may not come" [ 5 ] (see also [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%